What interventions are most effective for treating constipation in pregnancy or immediately postpartum?. Issue 4 (April 2017) - Harlin, Mallory; Morchen, Sarah
Abstract : EVIDENCE‐BASED ANSWER : A daily fiber supplement increases the frequency of defecation and leads to softer stools in pregnant women (SOR: A, based on systematic review of RCTs). Stimulant laxatives are more effective than bulk‐forming laxatives for treating constipation in pregnancy, but can cause uncomfortable side effects (SOR: A, based on systematic review of RCTs). Increased fluid intake is associated with less pregnancy‐related constipation (SOR: B, based on a prospective cohort study). Taking a probiotic supplement during pregnancy is associated with increased stool frequency (SOR: C, case series).